The Effect Of Corporate Social Responsibility And Profitability On Company Value (Study On Manufacturing Companies) - Bintang Mukhammad Burhanudin Akbar Akbar; Maulita Lutfiani Lutfiani (ICON Publisher, 2024)
The purpose of this study is to analyze the effect of corporate social responsibility and profitability on corporate value (a study on manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017). The results obtained indicate that CSR does not affect the value of the company, this is evidenced by the value of sig. calculate is greater than 0.05 which is 0.596> 0.05. Then the variable profitability affects the value of the company. This is evidenced by the value of sig. count is smaller than 0.05 which is 0.006 <0.05. CSR and profitability have an influence proportion on company value of 1.8% while the remaining 98.2% (100% - 1.8%) is influenced by other variables not in the linear regression model.